SEJARAH INDUSTRI KERAJINAN KAIN TENUN SONGKET CUAL (IKAT) DI DUSUN SEMBERANG KABUPATEN SAMBAS - Febrianti, Febrianti; Firmasyah, Andang; Putri, Astrini Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstract Thisresearch is entitled "The History of the Cual Ikat Songket Woven Craft Industry in Seberang Hamlet, Sambas Regency. The formulation of the problem in this study are: (1) How to make Songket Ikat Woven Fabrics in Sember Hamlet, Sambas Regency, (2) How is the production process of Songket Ikat Woven Fabrics in Seberang Hamlet, Sambas Regency, (3) How is the marketing process of the Woven Fabric Craft industry Songket Ikat in Dusun Sember, Sambas Regency from the past until now, (4) How to use Songket Ikat Woven Fabrics in Seberang Hamlet, Sambas Regency, (5) The motifs produced from Songket Ikat Woven Fabrics in Dusun Seberang, Sambas Regency. The method used in this research is the historical research method. The steps used in this historical research method consist of topic selection, heustrics, verification, interpretation, and historigraphy. With the aim of developing the craft of Songket Ikat Woven Fabrics to be better known by young people. In terms of economic and social development, the craft of Songket Ikat Woven Fabrics is quite developed, although from an economic point of view, the people of Dusun Semberang do not guarantee their lives, most of the weavers choose to become Indonesian Workers (TKI) in Malaysia and Brunei Darussalam, because being a TKI is promising economically. their economy. Meanwhile, from a social perspective, not all women can weave or want to weave, on average, weavers are housewives, whereas young people are rarely found who want to weave, according to them it is a boring thing, but for young people who want to weave. hobby and willing to learn. Keywords: Weaver, Economy, Social, Society